Intra-family nutrient sharing and factors affecting family dietary adequacy and nutritional status of children among low-income families in Barrio Paraiso San Francisco Del Monte, Quezon City. - Azares, Flora A.
This study was conducted to investigate nutrient sharing among family members and to determine the adequacy of food intakes. Likewise the effects of some family characteristics such as per capita income, family size, and education of the mother were determined statistically in relation to adequacy of family energy and protein intakes and to nutritional status of children, 0-10 years of age. The subjects were 38 families, composed of 202 members from an urban low-income community in Quezon City. The 24-hour food recall was used to record daily food intakes of all subjects, while height and weight data were used to indicate nutritional status of the children. The results showed that most family members had nutrient shares not in proportion to their needs indicating an inequitable nutrient distribution within the family. Age, sex, and social position of a member were factors found to influence nutrient sharing. The family heads, adult males and male school children were the most advantaged, while the male and female adolescents and the female pre-school children had the least share of the family food supply in relation to their needs. The main nutritional problem was inadequate food supply. The dietary intakes were inadequate both energy and protein foods, energy being more critical than protein. Energy dificiency was found to be due to inadequate fats and oils since the energy contribution of carbohydrates and proteins were inadequate. Apparently, the males had better diets. Based on the overall dietary evaluation, i.e. nutrient sharing, nutrient adequacy, and proportion of subjects 90 RDA, the adolescents, both male and female and the female pre-school children were the most nutritionally deprived. The adult male, male preschool children and the family heads were the most advantaged.
Thesis (Master of Science in Public Health, Nutrition)--University of the Philippines Manila.
Keywords: Nutrient sharing; Nutrition. -- Evaluation; Children -- Nutrition; Family nutrition